2005
DOI: 10.1159/000086063
|View full text |Cite
|
Sign up to set email alerts
|

Mycosis fungoides in European Russia: No Antibodies to Human T Cell Leukemia Virus Type I Structural Proteins, but Virus-Like Sequences in Blood and Saliva

Abstract: Objective: Mycosis fungoides (MF) is the most frequent form of cutaneous T cell lymphoma (CTCL). Human T cell leukemia virus type 1 (HTLV-1) involvement in MF progression is a matter of debate. The goal of the investigation was to search for HTLV-1 markers in a group of MF patients from a nonendemic area to HTLV-1. Materials and Methods: Fifty MF patients and 60 healthy donors from Moscow and the Moscow region were examined for HTLV-1 markers by Western blot, PCR, nested PCR, PCR/Southern hybridization, TaqMan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 92 publications
1
15
2
2
Order By: Relevance
“…Numerous etiological studies for this malignancy have focused on human T-lymphotropic virus (HTLV), immunosuppression, occupational factors, family history of cancer, and radiation exposure, but results were inconsistent or controversial [28,30]. Nevertheless, human T-lymphotropic virus, HIV, and Epstein-Barr virus Table 3 Percent distributions, incidence rates a and rate ratios of extranodal non-Hodgkin lymphomas b by race and cancer site in the selected areas c in the United States, 1999- (EBV) continue to be the suspected risk factors for this disease [31][32][33][34]. Incidence rates of peripheral T-cell lymphoma (PTCL) were about the same among men of all races whereas among women the rates were 18% higher among blacks than whites in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous etiological studies for this malignancy have focused on human T-lymphotropic virus (HTLV), immunosuppression, occupational factors, family history of cancer, and radiation exposure, but results were inconsistent or controversial [28,30]. Nevertheless, human T-lymphotropic virus, HIV, and Epstein-Barr virus Table 3 Percent distributions, incidence rates a and rate ratios of extranodal non-Hodgkin lymphomas b by race and cancer site in the selected areas c in the United States, 1999- (EBV) continue to be the suspected risk factors for this disease [31][32][33][34]. Incidence rates of peripheral T-cell lymphoma (PTCL) were about the same among men of all races whereas among women the rates were 18% higher among blacks than whites in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A consistent viral, environmental, or occupational causative factor or hereditary mutation has not been found (Ranki et al, 1990;Väkevä et al, 2000Väkevä et al, , 2005Burg et al, 2001;Girardi, 2004 review;Morozov et al, 2005;Pawlaczyk et al, 2005). Early conventional cytogenetic studies showed a large repertoire of chromosomal abnormalities in CTCL, both clonal and non-clonal, but no specific abnormality (Whang-Peng et al, 1982).…”
Section: Etiology General Remarksmentioning
confidence: 99%
“…(Manzari et al, 1987;Hall et al, 1991;Pancake et al, 1995;Bazarbachi et al, 1997;Wood et al, 1997;Morozov et al, 2005). A recent study using a method detecting virtually all known primate T-cell lymphotropic viruses (PTLVs) failed to identify any PTLVrelated sequence in a series of CTCL patients, confirming previous negative reports (Courgnaud et al, 2009).…”
Section: Electron Micrographs Of Sorted Cells (Supplementarymentioning
confidence: 66%